Employer Partnership Program Analysis of Alternatives - Pint, Ellen M. (RAND Corporation, 2012)
Launched by the U.S. Army Reserve, the Employer Partnership Program (EPP) supports reservists and their civilian employers. It features a job search website that allows employers to recruit among reservists, veterans, and family members. The study analyzed data collected through September 2010 from the EPP's job search website, conducted case studies of Army Reserve units located in four metropolitan areas, and interviewed program stakeholders.